"They gave me back my power": Strengthening older immigrants' language learning through arts-based activities. Issue 2 (3rd July 2021) - Balyasnikova, Natalia; Gillard, Spring
Abstract: Through the case of Jacqui, this article describes a community-based project called Seniors Thrive, which was intended to help immigrant seniors learn English, build social connections, and strengthen their leadership in order to support their health and well-being. The programming merged language learning and leadership opportunities through arts-based programming. Multiple classes offered through Seniors Thrive brought together individuals from all walks of life to learn together and from each other. As a result, many learners, including Jacqui, demonstrated heightened confidence in their English speaking abilities and increased their social connections. The arts-based program enabled the voices of older learners to be heard beyond their closed communities. We pose that arts-based activities have the potential to transform language learning in later life, if arts-based programs follow a flexible and community-driven design.